Effect of temperature, relative humidity and date of spawning on development of dry bubble disease (Verticillium fungicola (Preuss) Hassebr) in white button mushroom (Agaricus bisporus) - Jatav, Narendra Kumar; Rana, R S; Agrawal, Vijay Kumar; Tiwari, Girish Chand; Koli, Ram Swaroop (Mushroom Research, 2015)
Dry bubble disease of white button mushroom caused by Verticillium fungicola is prevalent in all mushroom growing areas in India causing heavy crop losses. In Haryana state, the white button mushroom is being cultivated on compost prepared by long method in low cost mushroom houses under seasonal conditions. High RH (90%) and low temperature (20Â°C) favoured the disease development. It has also been observed that under seasonal cultivation late spawning during the last week of October month favoured disease development causing maximum crop losses.